UPAYA PENINGKATAN PENGETAHUAN, SIKAP DAN KUNJUNGAN ANTENATAL CARE (ANC) IBU HAMIL MELALUI PEMBERDAYAAN KADER ANC - Sakinah, Vika; Fibriana, Arulita Ika (Unnes Journal of Public Health, 2015)
Antenatal Care (ANC) is a health service that health care professionals be given to pregnant women during pregnancy. ANC coverage can be monitored through K4 visits. Data in 2013, noted that Sumber health centers had the lowest K4 coverage in the Rembang district that was 71.91%. This research aims to increase the knowledge, attitudes and visit ANC through the empowerment of ANC cadres. This research was quasi experimental with nonequivalent control group design. Technique sampling used purposive sampling, that was as many as 15 experimental samples and 15 control samples. Hypothesis testing variables used Mann Whitney generate value of knowledge (p = 0,047), attitude (p = 0.003) and visits (p = 0.000). All test variables resulted in p value <0,05 so there was a meaningful difference between the groups with the empowerment of the ANC cadres with the group without empowerment of the ANC cadres. It was concluded that the empowerment of the ANC cadres can increase knowledge, attitude and ANC visit. Suggestions for the cadres are expected to implement programs and continue the cadres of the ANC.